Financial technology adoption on MSMEs sustainability: The mediating role of financial literacy and financial inclusion - Safii, Abdul Azis; Anom, Latifah; Murtini, Murtini (Publisher of Widyagama University of Malang (UWG Press), 2024)
This research examines how the adoption of financial technology impacts the sustainability of Micro, Small, and Medium Enterprises (MSMEs), emphasizing the intermediary roles of financial literacy and financial inclusion. A random sample of 288 MSME owners was chosen from the 1,020 members participating in the business legality assistance program by the Bojonegoro Regency Cooperative and MSME Service. Out of these, 247 owners fully completed the survey, providing data for the research. Data analysis utilized Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that although the adoption of financial technology positively influences MSME sustainability, the impact is relatively modest. However, financial literacy and financial inclusion considerably enhance this relationship, with financial literacy exhibiting a stronger mediating effect. These outcomes highlight the importance of specific financial literacy initiatives and better access to financial services to promote the sustainable growth of MSMEs.JEL ClassificationÂ L21; L26; O15